Lytic bony lesions on 18F-FDG PET-CT versus 99mTc MDP bone scan - Nida Rasheed; Mairah Razi (Journal of the Pakistan Medical Association, 2023)
With rising incidence of breast carcinoma in Asian population, staging workup remains a crucial entity in disease management and outcome. Bone scintigraphy for detection of osteoblastic metastasis has remained a convenient choice. However, in the presence of underlying lytic bony lesions sensitivity of 99mTc-MDP bone scan is questionable when compared to 18F-FDG PET-CT scan. We present a case that showed better sensitivity of 18F-FDG PET-CT for picking up early lytic lesions for staging breast cancer. Keywords: breast carcinoma, bone scan, 18F-FDG PET-CT.